2007
DOI: 10.1002/ijc.23153
|View full text |Cite
|
Sign up to set email alerts
|

MYCN regulates oncogenic MicroRNAs in neuroblastoma

Abstract: MYCN amplification is a common feature of aggressive tumour biology in neuroblastoma. The MYCN transcription factor has been demonstrated to induce or repress expression of numerous genes. MicroRNAs (miRNA) are a recently discovered class of short RNAs that repress translation and promote mRNA degradation by sequence-specific interaction with mRNA. Here, we sought to analyse the role of MYCN in regulation of miRNA expression. Using a miRNA microarray containing 384 different miRNAs and a set of 160 miRNA real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
188
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(213 citation statements)
references
References 38 publications
(43 reference statements)
22
188
0
3
Order By: Relevance
“…The functional overlap between MYCN and c-MYC is further substantiated by the identification of a c-MYC-translocated neuroblastoma tumor with a mRNA, miRNA and genomic profile that is typical for a MYCN-amplified tumor. It is also perfectly in line with previous reports on miRNAs commonly regulated by c-MYC and MYCN (Chen and Stallings, 2007;Chang et al, 2008;Sander et al, 2008;Schulte et and with the observation that MYCN can functionally replace c-MYC in murine development (Malynn et al, 2000). Whether c-MYC is capable of replacing MYCN remains to be determined but could further corroborate these findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The functional overlap between MYCN and c-MYC is further substantiated by the identification of a c-MYC-translocated neuroblastoma tumor with a mRNA, miRNA and genomic profile that is typical for a MYCN-amplified tumor. It is also perfectly in line with previous reports on miRNAs commonly regulated by c-MYC and MYCN (Chen and Stallings, 2007;Chang et al, 2008;Sander et al, 2008;Schulte et and with the observation that MYCN can functionally replace c-MYC in murine development (Malynn et al, 2000). Whether c-MYC is capable of replacing MYCN remains to be determined but could further corroborate these findings.…”
Section: Discussionsupporting
confidence: 91%
“…These small non-coding RNAs have an effect on virtually every aspect of tumorigenesis and function as negative regulators of messenger RNA (mRNA) levels and translation (Bartel, 2009). Some miRNAs, such as those belonging to the oncogenic miR-17-92 cluster, have been shown to be important players in MYCN/c-MYC signaling (O'Donnell et al, 2005;Dews et al, 2006;Chang et al, 2008;Fontana et al, 2008;Schulte et al, 2008;Northcott et al, 2009). However, a more general insight in the relationship between miRNAs and mRNAs within the MYCN/c-MYC transcriptional network remains to be examined.…”
Section: Introductionmentioning
confidence: 99%
“…In doxycycline (Dox)-free medium, Tet21N cells express exogenous MYCN in levels similar to common NB cell lines (16). We observed consistent upregulation of several MYC-associated miRNAs previously identified (17,18), including miRNAs from the oncogenic miR-17∼92 cluster (e.g., miR-17, miR-18a, and miR-19a) (19) and its paralogs on chromosome 7 and chromosome X (Fig. 1A, Fig.…”
Section: Expression Analysis Of Mirnas In Tet21n Cells Reveals Specifsupporting
confidence: 82%
“…Others have confirmed that miR-17/92 is regulated by N-myc, a direct target of SHH in CGNPs. 45 To further explore the relationship between SHH signaling, proliferation and miR-17/92, we treated mouse CGNPs with SHH or vehicle and profiled the cell lysates by miRNA microarray. These experiments confirmed miR-17/92 as a target of SHH signaling in CGNPs, an effect we determined to be mediated through N-Myc.…”
Section: Discussionmentioning
confidence: 99%